Life skills for effective teaching: Assessing the development of teaching skills in teacher trainees - Babu, Binu; Charles. M, Aron Antony (Edelweiss Applied Science and Technology, 2024)
As educational environments become increasingly complex, need for teachers to possess a diverse set of competencies beyond academic knowledge. This study aims to assess the impact of life skill development programs on the teaching skills of teacher trainees across urban and semi-urban areas of Kerala, incorporating a diverse representation from both public and private teacher training institutes. The target population comprises approximately 150-200 teacher trainees who have participated in life skill development activities as part of their curriculum. A range of statistical instruments were used to find the relation between variables such as life skill development activities, assessment methods, learning styles, and cohort size and teaching skills. To evaluate improvements in teaching skills across different life skill development activities Kruskal-Wallis H Test was used. Additionally, Spearman's rank-order correlation test assessed the relationship between training frequency and teaching skill enhancement. The Mann-Whitney U Test compared the effects of formative and summative assessment methods on perceived skill acquisition, and ANOVA analyzed the influence of learning styles on engagement and outcomes in life skill programs. Finally, the Chi-Square Test investigated the association between cohort size and interaction quality among teacher trainees. The results underscore the necessity for educational institutions to prioritize life skill development as a core component of teacher training programs, ultimately enhancing the quality of education and preparing teacher trainees for the challenges of contemporary classrooms.